ІСТОРИЧНІ ПОДІЇ ТА ЇХ ПЕРІОДИЗАЦІЯ У ЧАСОВОМУ ВИМІРІ: МЕТОДОЛОГІЧНА СИМПТОМАТИКА - Чучко, Михайло Костянтинович; Chuchko, Mykhailo; Боднарюк, Богдан; Bodnariuk, Bohdan (Науковий вісник Чернівецького національного університету імені Юрія Федьковича: Історія. Чернівці: Чернівецький університет, 2024. № 1. С.147–155, 2024)
The article examines a range of issues related to the essential features and characteristics of the definition of «event» in the temporal dimension, and also highlights the methodological symptoms of the content of historical periodization in the context of its functional tasks. The authors focus on the ambiguous and debatable problem of the research dichotomy – «event» and the temporal component from the point of view of constructing the historical space of the past. On the one hand, the event is studied as an element of historical analysis, on the other, the features of the process of its integration into the plane of the temporal organization of history. In addition, the authors consider the practical significance of what is happening at the level of basic chronological guidelines and categorical definitions. Another issue that is analyzed in the article is the modern understanding of historical narrative through the prism of new methodological approaches and interpretive models, which are based on two doctrinal positions: the first – history studies the process of human development, which has a general logic and direction, the second – this process is objective (in scientific sense) knowledge. At the same time, the authors emphasize the social conditionality of historical knowledge, which is understood primarily as aspects of an influential political situation and various ideological dominants. Finally, in the article the authors raise the topic of the causes and consequences of global categorical and conceptual «landslides» inherent in historical knowledge (historical opinion) of the 20th century. The main one is that the history of events has been replaced by the history of interpretations. As a result, the concept of «historical truth» has undergone partial methodological levelling and has lost a certain scientific relevance. As a result, the authors state the obviousness of the fact that event history in its «pure» form, which is understood as the sequential «walk» of events in a single, logically justified, chronological and causal connection, is quite conventional. It can be considered either as the simplest (elementary in its descriptiveness) form of historical discourse, or, from a modern point of view, as one of the extreme degrees of abstraction of historical analysis (in the dimension of subjective speculative constructions), since – within linear chronological time – it is not possible, in particular, to interpret the history of culture, philosophical or historiosophical doctrines (concepts), the history of collective ideas or the «history of the Other».
HISTORICAL EVENTS AND THEIR PERIODIZATION IN THE TIME DIMENSION: METHODOLOGICAL SYMPTOMATICS
ЧНУ
Keywords: methodology of history, methodological approaches, methodological problems, historical events, historical periodization, historical chronology, historical time, temporal representations, interpretation of events, narrative.